2021
DOI: 10.3390/cancers13092244
|View full text |Cite
|
Sign up to set email alerts
|

More Than Meets the Eye: Scientific Rationale behind Molecular Imaging and Therapeutic Targeting of Prostate-Specific Membrane Antigen (PSMA) in Metastatic Prostate Cancer and Beyond

Abstract: Prostate cancer is the second most common cancer type in men globally. Although the prognosis for localized prostate cancer is good, no curative treatments are available for metastatic disease. Better diagnostic methods could help target therapies and improve the outcome. Prostate-specific membrane antigen (PSMA) is a transmembrane glycoprotein that is overexpressed on malignant prostate tumor cells and correlates with the aggressiveness of the disease. PSMA is a clinically validated target for positron emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 160 publications
(194 reference statements)
2
13
0
Order By: Relevance
“…Prostate cancer can vary widely in the expression of PSMA. It is known that primary tumors and especially metastases can be PSMA-negative (34)(35)(36)(37)(38). This can also be the case for bone metastases (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer can vary widely in the expression of PSMA. It is known that primary tumors and especially metastases can be PSMA-negative (34)(35)(36)(37)(38). This can also be the case for bone metastases (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…PSMA is commonly used as a target for prostate cancer imaging and drug delivery. 117 , 118 , 119 , 120 , 121 As boron-containing inhibitors generally had high binding affinity to PSMA, Flavell and co-workers combined PSMA inhibitor scaffolds with boric acids/carborane derivatives, delivering boron into prostate cancer cells and prostate tumor xenograft models ( 20 , Figure 3 L). 119 The results showed that it was feasible to treat low-metastatic prostate cancer with PSMA containing boric acids or carboranes, thus demonstrating the potential role of PSMA in BNCT for the treatment of prostate cancer.…”
Section: Applications Of Carboranes As Boron Neutron Capture Therapy Agentsmentioning
confidence: 99%
“…PSMA has a large glycosylated extracellular domain responsible for its enzymatic activity, a transmembrane segment, and a short intracellular domain. The short cytosolic tail contains an internalization motif and interacts with various proteins enabling PSMA endocytosis [20]. The molecule is overexpressed in prostate cancer where it correlates with tumor aggressivity and vascularization and it is used as a target for radioconjugates for prostate cancer imaging (FDA approval in 2020) and recently also for therapy of advanced prostate cancer [12,13].…”
Section: Psma-an Effective Theranostic Targetmentioning
confidence: 99%